A stylistic and structural analysis of flute concerto by Krzysztof Penderecki - Karapınar, Filiz (Graduate School, 2023)
In this study, the artistic path and the important works of Krzysztof Penderecki (1933-2020) are examined. The majority of this thesis is concerned with a stylistic analysis of the Concerto for Flute and Chamber Orchestra (1992). This concerto is a recent example of Penderecki's current usage of stylistic synthesis. This study attempts to show how he employed diverse components within the context of a single piece of music and how Penderecki combined/synthesized the tradition and modernity regarding compositional techniques unique to this concerto. Through a rigorous stylistic, textural, and motivic examination, the study will assist to highlight the work's unifying compositional techniques. In addition, since the analysis of the flute concerto provides detailed information of its content and structural features, this study constitutes a source for flute students, musicologists, and performers. The study opens with a biographical sketch that reveals necessary information about Penderecki's varied compositional technique as well as his musical philosophy. Penderecki employed numerous compositional approaches while investigating a universal language. He explored diverse modern composing approaches, notations, styles, and genres, such as sonorism, serialism, and neo-Romanticism. Since the creation of Strophen in 1959 at the "Autumn of Warsaw" festival, he showed amazing courage in discarding all remains of musical history, as well as extraordinary ingenuity in finding undiscovered sound components of music, which immediately secured him a prominent position on the Polish musical scene and opened the way to international renown. As his compositions evolved, he progressively began to phase out avant-garde composing approaches. Throughout the 1980s, he discovered his own musical pluralism, a chromaticism that is largely polyphonic without tonality, but with themes and motifs that allow for counterpountal interaction. Penderecki smoothly blended such extremes into the mainstream of his particular musical language, which he termed "synthesis" thanks to his superior craftsmanship. The studies and interviews show that for Penderecki, the art must be rooted in a uniting experience. Thus, synthesis not only refers to a composition approach, but might also combine old themes with new musical techniques, or be a synthesis of contemporary and traditional techniques that would communicate directly to audiences. The first chapter also includes a discussion of Penderecki's literary work, Labyrinth of Time. Five Addresses for the End of the Millennium, a compilation of five speeches held between 1993 and 1996. It was written both as the composer's personal declaration on the condition of art at the turn of that century, and as a response to critics who, in the mid-1970s, criticized his shift from experimentation to a more melodic expression in his music. Here we understand that the Penderecki's labyrinth symbolizes his artistic journey between the past and present. The third chapter of this study explores the Concerto for Flute and Chamber Orchestra from a structural and stylistic point of view, and aims to explain how Penderecki combines his avant-garde and neo-Romantic approaches in his "synthesis" through this work. Penderecki claimed that he always wrote his own music, creating a language that he used to communicate with the audience that appealed to their cultural memory. The work integrates traditional compositional approaches that give a chance for addressing this bridge between the artist and the listener. The fundamental strategy to the research was inspired by Jan La Rue, Guidelines for Style Analysis 2nd edition, 1992, (first published in 1970 New York: W. W. Norton), which is introduced in detail at the beginning of the third chapter. LaRue has developed a concept of style that permits the careful examination of each musical element. The main technique entails separating the music into its constituent sound, harmony, melody, rhythm, and growth (acronym SHMRG) for analytical purposes, utilizing the author's concept formula. The results obtained by applying these guidelines for style analysis are summarized in the fourth section. The concerto covers musical materials which are built carefully on selected intervallic combinations with a tendency for dissonances such as minor seconds. These materials are repeated and developed throughout the entire piece creating the whole structure. Continuous transformations and development of the initial material create an expressive and dramatic tension. When Penderecki discusses tonality, he refers to tonal centralization as opposed to traditional major-minor tensions. In addition to the dense and heavy orchestration influenced by the Romantic composers, his mastery in contrapuntal writing is demonstrated in his polyphonic dialogues between single instrumental groups. His sonoristic experiences have influenced Penderecki's timbral imagination. He makes use of the flute's many tone colors by using extreme registers, varied articulations, and varying tempos. In a chamber-like approach, the solo flute is juxtaposed against a large orchestra in such a way that its textures remain mostly transparent. In conclusion, Concerto for Flute and Chamber Orchestra all in all exemplifies Penderecki's synthesis idea, which involves taking a few steps back from the parametric and sonic extremities of the past half-century, and looking at history as a whole to find possible creative steps forward. One cannot deny that this flute concerto is a significant contribution to the instrument's repertoire, while there is a lack of flute-centric concerti in the late modern repertoire. The resulting method of the analysis is particularly extensive and effective for flute performers, scholars and researchers interested in stylistic concerns within the context of broader artistic or historical studies.
Krzysztof Penderecki flüt konçertosunun stilistik ve yapısal analizi
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2023
Keywords: music analysis; müzik analizi; classical music; klasik müzik; flute; flüt